How to build a digital library - Witten, I. H. (Ian H.) (Morgan Kaufmann series in multimedia information and systems., 2010)
How to Build a Digital Library is the only book that offers all the knowledge and tools needed to construct and maintain a digital library, regardless of the size or purpose. It is the perfectly self-contained resource for individuals, agencies, and institutions wishing to put this powerful tool to work in their burgeoning information treasuries. The Second Edition reflects new developments in the field as well as in the Greenstone Digital Library open source software. In Part I, the authors have added an entire new chapter on user groups, user support, collaborative browsing, user contributions, and so on. There is also new material on content-based queries, map-based queries, cross-media queries. There is an increased emphasis placed on multimedia by adding a "digitizing" section to each major media type. A new chapter has also been added on "internationalization," which will address Unicode standards, multi-language interfaces and collections, and issues with non-European languages (Chinese, Hindi, etc.). Part II, the software tools section, has been completely rewritten to reflect the new developments in Greenstone Digital Library Software, an internationally popular open source software tool with a comprehensive graphical facility for creating and maintaining digital libraries. As with the First Edition, a web site, implemented as a digital library, will accompany the book and provide access to color versions of all figures, two online appendices, a full-text sentence-level index, and an automatically generated glossary of acronyms and their definitions. In addition, demonstration digital library collections will be included to demonstrate particular points in the book. to access the online content please visit, www.greenstone.org. Sketches the history of libraries-both traditional and digital-and their impact on present practices and future directions Offers in-depth coverage of today's practical standards used to represent and store information digitally in all settings Uses Greenstone, freely accessible open-source software-available with interfaces in major languages (including Spanish, Chinese, and Arabic) Written for both technical and non-technical audiences- covers the entire spectrum of media, including text, images, audio and video Web-enhanced with software documentation, color illustrations, full-text index, source code, and more